2014
DOI: 10.1021/ol500277u
|View full text |Cite
|
Sign up to set email alerts
|

The Benzoyl Peroxide Promoted Dual C–C Bond Formation via Dual C–H Bond Cleavage: α-Phenanthridinylation of Ether by Isocyanide

Abstract: The benzoyl peroxide-promoted α-phenanthridinylation of ether by isocyanide is developed, proceeding through dual C-H bond cleavage and dual C-C bond formation. The procedure tolerates a series of functional groups, such as methyl, fluoro, chloro, acetyl, methoxy carbonyl, cyano, and trifluoromethyl. Thus, it represents a facile pathway leading to 6-substituted phenanthridine derivatives. The addition of radical to the isonitrile followed by a radical aromatic cyclization is involved in this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Experimental Section General Procedure for Synthesis of 2-Isocyanobiphenyls. 2-Isocyanobiphenyls were prepared according to the reported method, 16 17 16 17 5-fluoro-2-isocyano-1,1'-biphenyl (1f), 18 and 4-(2-isocyanophenyl)pyridine (1g). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 CDCl 3 ) δ 160.1...…”
Section: Scheme 3 Postulated Reaction Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Experimental Section General Procedure for Synthesis of 2-Isocyanobiphenyls. 2-Isocyanobiphenyls were prepared according to the reported method, 16 17 16 17 5-fluoro-2-isocyano-1,1'-biphenyl (1f), 18 and 4-(2-isocyanophenyl)pyridine (1g). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 CDCl 3 ) δ 160.1...…”
Section: Scheme 3 Postulated Reaction Pathwaymentioning
confidence: 99%
“…Both decreasing temperature and exposure to air negatively affected the reaction (Table 1, entries [9][10]. In addition, we attempted to examine the effects of different solvent systems on the model reaction (Table 1, entries [11][12][13][14][15][16][17], but none of the other solvent systems were effective for this transformation. These results showed that the optimized conditions were 3.0 equiv of K 2 S 2 O 8 with 1.5 equiv of K 2 CO 3 in CH 3 CN/H 2 O (v/v = 1/1) at 80 °C under Ar for 1 h. We next investigated the scope and generality of the reaction under optimized conditions.…”
mentioning
confidence: 99%
“…[1] Specifically,t he radical relay cyclization provides ap owerful synthetic alternative to rapidly access denselyf unctionalized cyclic molecular frameworks. [1] Specifically,t he radical relay cyclization provides ap owerful synthetic alternative to rapidly access denselyf unctionalized cyclic molecular frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Radicalr elays trategy is of current research interest and has been recognized as ah igh-efficient synthetic methodf or the synthesis of complex bioactive molecules due its excellent functional group tolerance. [1] Specifically,t he radical relay cyclization provides ap owerful synthetic alternative to rapidly access denselyf unctionalized cyclic molecular frameworks. [2] Such transformation could avoid the time and cost consuming prefunctionalizations, therebyf eaturing step and atom economy with environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In synthetic organic chemistry, BPO acts as an effective radical initiator for promoting the polymerization and aromatic cyclization reactions. [6][7][8][9] However, the widespread applications of BPO may cause many side effects. For example, excessive addition of BPO in food can induce allergic reactions, leading to the degeneration of carotene and other nutrients.…”
Section: Introductionmentioning
confidence: 99%